Chicory abrogates oxidative stress, inflammation and caspase-dependent apoptosis in acute hepatic injury model induced by acetaminophen in rats - Mohamed Elsayed Nady,; Ahmed M. Mansour,; Elsayed E. Hafez,; Gamal Omran,; Gamal M. Hamad,; Sahar E. Harraz,; Shady N. Allam,; Ali A. Ahamad, (International Journal of Phytomedicine, 2016)
In this study the protective effect of chicory leaves hydroalcoholic extract (CIE) against acute liver injury induced by a single dose of acetaminophen (700 mg/kg, i.p.) was investigated in rats. The CIE and silymarin treatment (standard reference) were given in a dose of (100 mg/kg, p.o.) for 3 days before and at 1 and 12 h following acetaminophen administration. Treatment with CIE signiﬁcantly reduced the levels of serum ALT, AST, alkaline phosphatase, bilirubin, total cholesterol, triglycerides, urea, creatinine, TNF-α and hepatic contents of malondialdehyde (MDA), nitric oxide, caspase-3 and hydroxyproline, with significant increases in serum total protein, albumin, HDL- cholesterol and hepatic activities of reduced glutathione (GSH), superoxide dismutase (SOD) and catalase (CAT) as compared with the acetaminophen group. The histopathological alterations mediated by acetaminophen were ameliorated by CIE. It was concluded that CIE protects rat liver against acetaminophen hepatotoxicity, most probably through abrogation of oxidative stress, inflammation and caspase-3 dependent apoptosis.